2023
DOI: 10.1021/jacs.3c07031
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Redox Activity of Organonickel Radical Complexes Governed by the Geometry

Gregory A. Dawson,
Qiao Lin,
Michelle C. Neary
et al.

Abstract: Nickel-catalyzed cross-coupling reactions often employ bidentate πacceptor N-ligands to facilitate radical pathways. This report presents the synthesis and characterization of a series of organonickel radical complexes supported by bidentate N-ligands, including bpy, phen, and pyrox, which are commonly proposed and observed intermediates in catalytic reactions. Through a comparison of relevant analogues, we have established an empirical rule governing the electronic structures of these nickel radical complexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 48 publications
2
24
0
Order By: Relevance
“…Our study on (pyrox)Ni complexes indicates that the redox activity of a ligand can vary among different complexes (Scheme ). This observation remains consistent across a range of reported organonickel radical complexes ligated with bidentate N -ligands . By analyzing data from the literature combined with our results, we established a general framework for understanding the ligand redox activity of nickel radical complexes .…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…Our study on (pyrox)Ni complexes indicates that the redox activity of a ligand can vary among different complexes (Scheme ). This observation remains consistent across a range of reported organonickel radical complexes ligated with bidentate N -ligands . By analyzing data from the literature combined with our results, we established a general framework for understanding the ligand redox activity of nickel radical complexes .…”
Section: Introductionsupporting
confidence: 85%
“…Soc. 2023 , 145 , 20551–20561 . A collection of well-defined nickel radical complexes that reveals an empirical correlation between coordination geometry and ligand redox activity.…”
Section: Key Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Other sacrificial anode materials, such as Al and Mg, resulted in premature reaction termination. NaI served a dual role as both a reaction additive and optimal electrolyte for the system, thereby giving rise to superior yields and enantioselectivities compared with other electrolytes like TBAI, TBAPF 6 , and NaPF 6 . When no current was passed, the product was obtained in 2% yield, which suggested that electricity was required to overcome the overpotential of the cell.…”
Section: Synthetic Methods Developmentmentioning
confidence: 99%